Social Media User in Receiving and Sharing Hoax Information: Overview from Motivation Level - Melisa Arisanty; Niken Febrina; Gunawan Wiradharma; Eraskaita Ginting (FISIP Universitas Islam Negeri Raden Fatah Palembang, 2022)
Social media is a very vulnerable medium for the spread of hoax information. Based on various research survey references, social media currently remains the main source of circulating hoaxes. Ironically, many hoax information that is spread can cause unrest, conflict, slander, overthrow each other, and excessive fear. On the other hand, the characteristics of social media make it easier for users to share information on their social networks. With a description of the problem conditions regarding the spread of hoax information that is very complex, it is necessary to increase social media users' awareness and information literacy. However, the strategy to increase the awareness of social media users is not easy to formulate. In advance, it is necessary to know the biggest motives of social media users in receiving and redistributing hoax information. Based on research using a quantitative approach through a cross-sectional survey strategy, it has been found that the motives that most often underlie social media users in receiving hoax information are dominated by the information exposure process motive and the viral information motive. In addition, someone's motive for sharing hoax information is the motive for low information literacy and cultural motives for sharing information.